Theoretical and practical aspects of pedagogy and psychology - Moskatova A. K., Gordeeva E. N., Lavina T. A., Zakharova A. N., Gritskevich T. I., Goriachevskaia E. V., Safonova M. V., Levchenko V. V., Lapshova E. S., Meshechkina R. P., Vysochinenko A. S., Ustinova E. M., Shilenko S. I., Zaritskaia V. V., Dzokaeva Z. M., Pavliuchenok M. B., Uliankova N. A., Sokolova G. A., Genvareva I. A., Marchenkova N. G., Leont'eva L. N., Sudakov O. V., Sudakov D. V., Belov E. V., Gordeeva O. I., Kretinina L. V., Sorokoumova G. V., Mychko E. I., Strelnikova E. S., Kumaeva M. V., Bulat R. E., Sharipova A. P. (Theoretical and practical aspects of pedagogy and psychology, 2022)
the study was conducted on the basis of the Department of Traumatology with the course of disaster Medicine of the Amur State Medical Academy of the Ministry of Health of Russia. The article discusses the use of interactive forms of learning in teaching the discipline «Life safety», the main functions of pedagogical reflection and digital transformation of modern teachers are given.
Keywords: интерактивное обучение; безопасность жизнедеятельности; инклюзия; цифровизация образования; digitalization of education; life safety; interactive learning; inclusion; электронно-информационная образовательная среда; electronic information educational environment